2012 4th Conference on Data Mining and Optimization (DMO) 2012
DOI: 10.1109/dmo.2012.6329811
|View full text |Cite
|
Sign up to set email alerts
|

Is artificial immune system suitable for opinion mining?

Abstract: Opinion mining is used to automate the process of identifying opinion whether it is a positive or negative view. Majority of previous works on this field uses natural language programming techniques to identify the sentiment. This paper reports the use of artificial immune system (AIS) technique in identifying Malaysian online movie reviews. This opinion mining process uses three string similarity functions namely Cosine Similarity, Jaccard Coefficient and Sorensen Coefficient. In addition, AIS performance was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…Their findings showed that an SVM trained on a unigram bag-of-words feature set outperforms all other approaches presented in their work. Samsudin et al (2012) reported the use of the Artificial Immune System (AIS) technique in classifying Malaysian online movie reviews into negative and positive sentiments. The AIS performance was compared with other traditional machine learning techniques.…”
Section: Supervised Machine Learning Approachmentioning
confidence: 99%
“…Their findings showed that an SVM trained on a unigram bag-of-words feature set outperforms all other approaches presented in their work. Samsudin et al (2012) reported the use of the Artificial Immune System (AIS) technique in classifying Malaysian online movie reviews into negative and positive sentiments. The AIS performance was compared with other traditional machine learning techniques.…”
Section: Supervised Machine Learning Approachmentioning
confidence: 99%
“…As long as a document classification problem can be represented as a binary string, the system can learn a classifier from a set of training instances. Additionally, there are more recent works which study the convenience of using AIS for opinion mining [34], and use this kind of techniques for selecting features for opinion mining [35] or analysing sentiments in newspapers [31].…”
Section: Related Workmentioning
confidence: 99%